(untitled) (Research, Society and Development, 2021)
Anthropocene is the current geological age in which profound environmental changes on the planet occur under the influence of human activities. Among other aspects, some that corroborate this scenario are the food production system, including the impact of food losses and the generation of agro-industrial residues, as well as the consumption and disposal of plastics on a large scale, with particular attention to materials with a short life cycle, such as food packaging. As a result, there is a growing demand for packaging from renewable sources that are biodegradable and contribute to adding value and minimizing food loss, increasing its shelf life and functional value. An alternative that has been explored to improve the mechanical, thermal, and barrier properties of films is the use of nanoparticles which, due to the nanometric scale, provide the films with improved characteristics, such as higher tensile strength and Young’s modulus and lower vapor permeability of water when compared to biodegradable films without nanoreinforcement. Nanoparticles can also be produced from agro-industrial residues, such as banana, cassava, corn peels, grape pomace, mango seeds and, cashew residues. Thus, this review aims to contribute to knowledge about the valorization of vegetables and their residues through the development of more sustainable films and food packaging, with a greater focus on studies produced by Brazilian institutions using national raw materials.